Researchers’ Perspectives on Digital Mental Health Intervention Co-Design With Marginalized Community Stakeholder Youth and Families - Porche, Michelle V.; Folk, Johanna B.; Tolou-Shams, Marina; Fortuna, Lisa R. (Frontiers in Psychiatry, 2022)
Co-design of digital mental health technology with youth and families is a relatively new but growing approach to intervention development. In this perspective paper, researchers used collaborative reflexivity through duoethnography methodology to reflect and report on experiences and lessons learned conducting co-designed projects with marginalized youth and families. Researchers engaged in written reflective dialogue regarding projects designed to co-develop technology-based apps and computer programs to support mental health of youth and their families. Reflections described the barriers and challenges for sharing responsibilities with stakeholders who have extensive lived experience but limited exposure to research. Researchers shared insights about their own intersectionality and positionality from marginalized to privileged, relative to co-design participants, and what it means to share authority, authentic partnership, and responsibility in the research process. Cultural understanding may diverge, even between acculturated minority researchers and matched minority stakeholders. While there are a variety of approaches that researchers might refer to as co-design, it is important to be intentional in the implementation of these processes so that collaborations with stakeholder youth and families are neither disingenuous nor exploitative. Implications for equitable and meaningful engagement of marginalized communities in co-design projects for youth mental health are discussed.